2019
DOI: 10.1016/j.jtcvs.2018.08.117
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide provides myocardial protection when added to the cardiopulmonary bypass circuit during cardiac surgery: Randomized trial

Abstract: Objectives: The aim of this pilot study was to elucidate the effects of exogenous nitric oxide (NO) supply to the extracorporeal circulation circuit for cardioprotection against ischemia-reperfusion injury during coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB).Methods: A total of 60 patients with coronary artery disease scheduled for CABG with CPB were enrolled in a prospective randomized study. Patients were allocated randomly to receive treatment according to standard or modified CPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 29 publications
1
20
0
4
Order By: Relevance
“…Forty-eight studies were excluded due to lack of full text, not randomized for NO therapy or crossover studies, not reporting renal outcomes, and using peritoneal dialysis as readily therapy. Finally, six studies were eligible for systematic review [18, 19, 21, 22, 31, 32]. Among the six included studies, one study was ultimately excluded, because not all the patients in NO and control groups underwent CPB [32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-eight studies were excluded due to lack of full text, not randomized for NO therapy or crossover studies, not reporting renal outcomes, and using peritoneal dialysis as readily therapy. Finally, six studies were eligible for systematic review [18, 19, 21, 22, 31, 32]. Among the six included studies, one study was ultimately excluded, because not all the patients in NO and control groups underwent CPB [32].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies started NO therapy immediately before CPB weaning [21, 22] and defined renal dysfunction as urine output less than 0.3 ml/h [21] or need for renal replacement treatment (RRT) [22], respectively. Three studies delivered NO from the beginning of CPB and defined AKI by the KDIGO criteria [18, 19, 31]. Detailed information of all included studies is shown in Table 1, and quality evaluation is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies clearly demonstrated that the deficiency of endothelial NO-synthase exacerbates myocardial IRI, whereas its overexpression, the administration of NO donors, and the inhaled NO, all protect the myocardium [ 27 , 28 , 29 ]. NO is an important key mediator and trigger in cardio protection afforded by both early and late ischemic preconditioning [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia-reperfusion injury during cardiopulmonary bypass (CPB) is inevitable, and the quest to ameliorate this injury has been pursued for decades. In their study in this issue of the Journal, Kamenshcikov and colleagues 1 have taken on this challenge, hypothesizing that nitric oxide (NO) in the cardiopulmonary bypass circuit will reduce myocardial injury during coronary artery bypass grafting (CABG) surgery. The salutary effects of NO have been the subject of intense investigation, which indeed culminated with the Nobel Prize in Medicine in 1998.…”
mentioning
confidence: 99%